The Ideological and Ontological Causes of Russia’s War on Ukraine. West versus East; Tyranny versus Democracy - Hordiichuk, Olha (ETHICS IN PROGRESS, 2023)
The article deals with the causes of Russia’s war on Ukraine, which is based on political and geopolitical interests, economic and military strategies, ambitions of individual political leaders, and mentality factors. The ontological basis of the war is the historically formed fundamental difference between the spiritual world, mentality traits of Ukrainians and Russians, which formed under the influence of a particular culture, with its ethnic, value and worldview coordinates, and under the influence of ideologies that determined the features of social and political life at different historical times. A strong spiritual system is created in the social and cultural space of the state, which preserves its values from generation to generation in the culture, forming a stable mentality and enduring attitudes. Their conceptual comprehension expands the context of cause-and-effect connections, helps to understand the situation more deeply and to choose optimal effective mechanisms for gradually successfully resolving the complex geopolitical situation that threatens the whole world.